From Likes to Saving Lives: Embracing Social Media's Power to Connect, Learn, and Innovate in Medical Education Delivery - Bankar Nandkishor J; Shrivastava Prateek Saurabh; Gajbe Ujwal; Singh Brij Raj; Tiwade Yugeshwari; Bandre Ankit (Wolters Kluwer Medknow Publications, 2024)
Social media have become an integral part of human life, because the manner in which we communicate, share information, and network with the external world is changing significantly. The purpose of the current review is to explore the role of social media in transforming medical education, identify the merits and the potential concerns, and propose effective strategies to overcome the identified challenges. Social media have significant potential in strengthening the delivery of medical education and meeting the scenarios emerging out of changing dynamics. The most important aspect of social media is that they have global reach and wide accessibility, and promotes active engagement of students. Similar to any other teaching-learning method, even the use of social media has its own limitations-cum-concerns. We must come out with potential solutions to each one of these problems so that overall acceptance and utilization of social media applications can be optimized. In conclusion, social media in medical education have immense potential to revolutionize learning and provide a platform for collaborative learning and networking. The need of the hour is to do systematic planning, train stakeholders, and establish guidelines for promoting effective engagement while using social media, and thereby keeping pace with the rapidly evolving healthcare landscape.